2023
DOI: 10.1097/mol.0000000000000876
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypercholesterolemia: The nexus of endothelial dysfunction and lipoprotein metabolism in COVID-19

Abstract: Purpose of reviewPatients with heterozygous familial hypercholesterolemia (HeFH) are at increased risk for COVID-19 cardiovascular complications in the acute phase of the infection. Elevated levels of LDL-C and often lipoprotein(a) are present from birth and lead to endothelial dysfunction, which is aggravated by a direct viral attack of the endothelial cells and their exposure to the toxic levels of circulating proinflammatory and prothrombotic mediators during the hyperinflammatory reaction typical of COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Moreover, individuals with heterozygous familial hypercholesterolemia face heightened risks of cardiovascular complications in the acute stage of COVID-19 infection. During the heightened inflammatory response in COVID-19 pneumonia, elevated LDL-C levels can exacerbate endothelial dysfunction and promote the release of prothrombotic mediators (Vuorio et al, 2023). Another study indicates that patients who has minimal LDL-C upon admission are more prone to immune and inflammation dysfunction, as well as multi-organ dysfunction (Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individuals with heterozygous familial hypercholesterolemia face heightened risks of cardiovascular complications in the acute stage of COVID-19 infection. During the heightened inflammatory response in COVID-19 pneumonia, elevated LDL-C levels can exacerbate endothelial dysfunction and promote the release of prothrombotic mediators (Vuorio et al, 2023). Another study indicates that patients who has minimal LDL-C upon admission are more prone to immune and inflammation dysfunction, as well as multi-organ dysfunction (Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, epidemiologic research showed that acute myocardial infarction is increased in COVID-19–infected heterozygous familial hypercholesterolemia patients, which is suggested that the risk for acute cardiovascular events is increased in the long-term. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Since the risk caused by reinfection builds on the residual risk caused by the first infection, the cardiovascular consequences of the first infection in the general population and the relatively rare autosomal dominant disorder familial hypercholesterolemia (FH) will be presented first. Previously, we have summarized the current understanding of the high vulnerability of FH patients to the first SARS-CoV-2 infection, with endothelial dysfunction supposedly playing a noticeable role in the generation of adverse clinical consequences [ [5] , [6] , [7] , [8] ]. Although we focus on the clinical pieces of evidence showing that COVID-19 infection raises the risk for cardiovascular diseases and their complications, we also recognize that patients suffering from cardiovascular diseases are more prone to SARS-CoV-2 infection, revealing that such a two-way connection between viral infections and cardiovascular disease risk may exist [ 9 ].…”
Section: Introductionmentioning
confidence: 99%